2010
DOI: 10.1007/s00280-010-1327-8
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab and circadian chronomodulated chemotherapy as salvage treatment for metastatic colorectal cancer (mCRC): safety, efficacy and improved secondary surgical resectability

Abstract: The addition of cetuximab to chronotherapy allowed safe and effective therapeutic control of metastases, including their complete resection, despite previous failure of several treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 44 publications
2
42
0
1
Order By: Relevance
“…In mice, at the time of maximal DNA synthesis (mid-activity) maximal mortality is noticed and in midrest phase (DNA synthesis minimum) maximum tolerability is noticed for 5-florouracil treatment (Lévi et al 2011). Phase I, II and III clinical trials carried out in humans; Lévi et al (2011) revealed that the administration of chemotherapeutic agents at a time of day corresponding to peak tumour sensitivity can produce distinct therapeutic benefits for cancer patients. Assessment of individual rhythms (activity-rest cycle by actigraphy) is obligatory for chronotherapy to assess the individual's body clock (Lévi et al 2011).…”
Section: Chronotherapeutics Of Cancermentioning
confidence: 97%
See 2 more Smart Citations
“…In mice, at the time of maximal DNA synthesis (mid-activity) maximal mortality is noticed and in midrest phase (DNA synthesis minimum) maximum tolerability is noticed for 5-florouracil treatment (Lévi et al 2011). Phase I, II and III clinical trials carried out in humans; Lévi et al (2011) revealed that the administration of chemotherapeutic agents at a time of day corresponding to peak tumour sensitivity can produce distinct therapeutic benefits for cancer patients. Assessment of individual rhythms (activity-rest cycle by actigraphy) is obligatory for chronotherapy to assess the individual's body clock (Lévi et al 2011).…”
Section: Chronotherapeutics Of Cancermentioning
confidence: 97%
“…A well-tailored chronopharmacological strategy can improve tumour response, overall survival and minimize side effects and toxicity in cancer patients rather than randomized clinical trials (Nakagawa et al 2006). In mice, at the time of maximal DNA synthesis (mid-activity) maximal mortality is noticed and in midrest phase (DNA synthesis minimum) maximum tolerability is noticed for 5-florouracil treatment (Lévi et al 2011). Phase I, II and III clinical trials carried out in humans; Lévi et al (2011) revealed that the administration of chemotherapeutic agents at a time of day corresponding to peak tumour sensitivity can produce distinct therapeutic benefits for cancer patients.…”
Section: Chronotherapeutics Of Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…85 More recent studies have shown that biological predictors of responsiveness to specific therapeutic agents (eg, K-ras mutational status as a predictor of responsiveness to cetuximab) may be highly informative prognostic variables. [86][87][88] Prognostic Systems…”
Section: Hepatic Colorectal Adenocarcinoma Metastases Overviewmentioning
confidence: 99%
“…Sixteen patients (17.6%) had received all the five major drugs. Twenty patients received chronomodulated chemotherapy (21%) [10]. In the 84 pretreated patients, 6 complete responses (CR) and 26 partial responses (PR) were reported to the last regimen, for an overall response rate (ORR) of 38.1%.…”
Section: Patientsmentioning
confidence: 99%